2020
DOI: 10.1177/0194599820949528
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Training: Misunderstandings of Airway Management in Medical Students and Internal Medicine Residents

Abstract: Objectives (1) Evaluate baseline airway knowledge of medical students (MSs) and internal medicine (IM) residents. (2) Improve MS and IM resident understanding of airway anatomy, general tracheostomy and laryngectomy care, and management of airway emergencies. Methods A before-and-after survey study was carried out over a single academic year. MS and IM resident knowledge was evaluated before and after an educational, grand rounds–style lecture reviewing airway anatomy, tracheostomy tube components, tracheostom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Tokarz and colleagues' assessment of medical students and residents found that 25% would choose to orally intubate a hypothetical patient with a laryngectomy or occlude the stoma and supplement with oral/nasal oxygen. 13 The proportion choosing these potentially fatal options, which might be appropriate for a patient with a tracheostomy, did not improve with an increased level of clinical training, whereas a targeted educational intervention proved effective. Despite significant structural differences between the United States and United Kingdom, 14 we identified significant parallels across geographies in the challenges faced around management of laryngectomy cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tokarz and colleagues' assessment of medical students and residents found that 25% would choose to orally intubate a hypothetical patient with a laryngectomy or occlude the stoma and supplement with oral/nasal oxygen. 13 The proportion choosing these potentially fatal options, which might be appropriate for a patient with a tracheostomy, did not improve with an increased level of clinical training, whereas a targeted educational intervention proved effective. Despite significant structural differences between the United States and United Kingdom, 14 we identified significant parallels across geographies in the challenges faced around management of laryngectomy cases.…”
Section: Discussionmentioning
confidence: 97%
“…As the number of total laryngectomies decreases due to organ preservation surgery and chemoradiation, 11 , 12 physicians, nurses, and allied health professionals encounter these advanced surgical airways less frequently, and associated knowledge and familiarity decline. Tokarz and colleagues’ assessment of medical students and residents found that 25% would choose to orally intubate a hypothetical patient with a laryngectomy or occlude the stoma and supplement with oral/nasal oxygen 13 . The proportion choosing these potentially fatal options, which might be appropriate for a patient with a tracheostomy, did not improve with an increased level of clinical training, whereas a targeted educational intervention proved effective.…”
Section: Discussionmentioning
confidence: 99%
“…Tokarz et al demonstrated that, among internal medicine and emergency medicine residents who have cared for patients with tracheostomy or laryngectomy, less than half were able to correctly address basic airway emergencies. 17 When primed with formal tracheostomy education, residents performed better following clinical rotations than their peers who attended rotations without a tracheostomy training course. 16 Therefore, formal education on airways and tracheostomy is a necessity in early medical education.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, previous studies have shown low confidence and knowledge levels with tracheostomy care in nonotolaryngologic providers. 2 , 14 - 17 …”
mentioning
confidence: 99%
See 1 more Smart Citation